2023
DOI: 10.1101/2023.01.05.23284180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral Azvudine (FNC) Tablets in Patients infected with SARS-CoV-2 Omicron Variant: A Retrospective Cohort Study

Abstract: Background: There is a lack of data on the efficacy of oral Azvudine in Coronavirus Disease treatment. This study aimed to assess the association between Azvudine treatment and clinical outcomes in a cohort of patients infected with the SARS-CoV-2 Omicron variant. Methods: This is a retrospective study conducted in two mobile cabin hospitals. All consecutive patients with a diagnosis of COVID-19 admitted from August to October 2022 were included in the study. Linear regression models and Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Although there are some acceptable efficacy and safety profiles of azvudine for treating COVID-19, evidence investigating its real-world outcomes is scarce. Only three real-world reports that compare azvudine with placebo have been published [ 23 ] or posted on the MedRxiv website for public comment [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some acceptable efficacy and safety profiles of azvudine for treating COVID-19, evidence investigating its real-world outcomes is scarce. Only three real-world reports that compare azvudine with placebo have been published [ 23 ] or posted on the MedRxiv website for public comment [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 Several studies demonstrated that Azvudine could reduce the duration of virus clearance and improve the clinical prognosis in COVID-19 patients including those with pre-existing comorbidities. 5 , 6 , 7 , 8 Therefore, concerns arise about the clinical effectiveness of Azvudine versus Paxlovid in COVID-19 patients with pre-existing comorbidities on admission.…”
mentioning
confidence: 99%
“…Since government policy and clinical expert guidelines recognized oral Azvudine treatment as a standardized treatment protocol for patients with COVID-19, Azvudine treatment has been widely used in China. Recent studies have shown that oral Azvudine treatment not only shortened the time to the first negative nucleic acid test results [ 15 , 16 , 21 , 22 ], but also reduced the risks of the accompanying disease progression outcome and all-cause death, especially for male patients with COVID-19 [ 6 , 17 , 23 ]. Additionally, Azvudine treatment improved the function of immune cells in monkeys [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of eosinophil cells is reduced and gradually recovers to normal after optimal treatment of COVID-19, which could be a useful indicator for the degree of COVID-19 [ 14 ]. With regard to the effectiveness of Azvudine treatment, it not only contributes to reducing the viral shedding time [ 15 , 16 ], but is associated with lower risks of severe complications and all-cause-death in patients with COVID-19, especially in male patients [ 17 ]. A recent study showed that there was a sharp increase in alive CD4 + and CD8 + T cells in the thymus of monkeys after Azvudine treatment, which contributed to the improvement of immune cells functions in the thymus [ 18 ].…”
Section: Introductionmentioning
confidence: 99%